Effects of Anulom Vilom Pranayama and Rope Mallakhamb Training on respiratory parameters in young females with athletic backgrounds - Julien S. Baker; Baljinder S. Bal; Rashmi Supriya; Parmjit Kaur; Maman Paul (IP Iermakov S.S., 2022)
Background and Study Aim. To assess the effects of Anulom Vilom Pranayama (AVP) or alternative nostril breathing and Rope Mallakhamb Training (RMT) on respiratory parameters among university females with athletic backgrounds. Material and Methods. A quasi experimental study was performed on thirty-six, university female students from the Department of Physical Education (T), Guru Nanak Dev University, Amritsar, Punjab, India. The subjects were divided in three groups. The groups were subjected to 4-weeks of intervention including: Group A (n1=12) subjected to AVP, Group B (n2=12) subjected to RMT, and Group C: (n3=12) no training or control. Respiratory parameters were measured twice, pre and post intervention using a wet spirometer. All measurements were performed three times and the average values were recorded for analysis. Results. 4-weeks of AVP resulted in positive increases for respiratory parameters measured including Tidal Volume (VT) 25.7%, Inspiratory Reserve Volume (IRV) 29.4%, Expiratory Reserve Volume (ERV) 27.1%, Vital Capacity (VC) 33.2%, and Inspiratory Capacity (IC) 31.6% compared to the control group. Also, 4-weeks of RMT had a positive impact on respiratory parameters including (VT) 19.8%, (IRV) 22%, (ERV) 19.4%, (VC) 32 % and (IC) 28.1% compared to the control group. Conclusions. Both AVP and RMT had a positive impact on respiratory parameters. Also, AVP training has a more positive impact on respiratory parameters than RMT and may also contribute to the enhancement of concentration-based performance and voluntary control of breathing among young females from athletic backgrounds. As a result, AVP training can be more beneficial for a competitive edge in order to improve the athletes' primary need for respiratory endurance.